2013
DOI: 10.1002/cbic.201300271
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Screening: An Effective Approach for Probing the Substrate Space of Uncharacterized Cytochrome P450s

Abstract: Cytochrome P450 monooxygenases (P450s) are versatile enzymes with high potential for biocatalysis. The number of newly annotated P450 genes has been increasing constantly, and these thus represent a rich resource for new biocatalysts. However, the substrate scopes of newly identified P450s are often not known, and thus their exploitation is difficult. Herein we describe an approach, named "cluster screening", and its application for the primary characterization of two P450s: CYP154E1 and CYP154A8. A library co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 43 publications
0
48
0
Order By: Relevance
“…We also provide another way to access the primary (+)‐nootkatone alcohol 3 . Previous studies have shown only allylic hydroxylation products 3 and 26 and the epoxide 25 (Scheme ) . Oxidation of 6 leads even to a greater variety of described products.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We also provide another way to access the primary (+)‐nootkatone alcohol 3 . Previous studies have shown only allylic hydroxylation products 3 and 26 and the epoxide 25 (Scheme ) . Oxidation of 6 leads even to a greater variety of described products.…”
Section: Resultsmentioning
confidence: 96%
“…The products identified in this study and the enzymes used are shown in bold. The other derivatization studies of 1 to 3 , 25 , and 26 were conducted by Sowden et al., by Kolev et al., and by von Bühler et al …”
Section: Resultsmentioning
confidence: 99%
“…Recently we reported on CYP154E1 from Thermobifida fusca YX that accepts a broad range of substrates including geraniol which is converted to 8-hydroxygeraniol [30]. In the present work several further acyclic terpenoids were screened as possible substrates for CYP154E1 and the regio- and chemoselectivity of their oxidation was investigated.…”
Section: Introductionmentioning
confidence: 96%
“…In fact, Berrie et al purified and characterized this P450 enzyme (24). Very recently, Von et al reported on the substrate screening of two CYP154 enzymes, CYP154E1 of T. fusca and CYP154A8 of N. francinica (25). CYP154E1 and CYP154A8 oxidize many compounds, including saturated fatty acids, primary alcohols, and terpenoids.…”
mentioning
confidence: 99%